Improving Students' Speaking Ability through Scaffolding Technique - Gede Ginaya; I Nyoman Rajin Aryana; Ni Putu Somawati (Politeknik Negeri Bali, 2018)
Students often got confused and felt hesitant when they speak English. This situation had caused poor speaking ability, which then lead to serious problem in the teaching-learning process. The application of scaffolding technique in the EFL learning might be the ideal solution; it had some principles that could improve the students’ speaking ability. This research is aimed at finding out the effect of the implementing Scaffolding Technique towards the students’ speaking ability. Participants were 50 (27 males and 23 females) third-semester students, enrolled in a three-year diploma program in Travel and Tourism Business, State Polytechnic of Bali in 2017/2018 academic year. The students in the experimental group were given communicative activities such as brainstorming, business games, simulation, WebQuest, problem-solving, which were carefully designed to necessitate the implementation of the scaffolding technique. The students in the control group were taught by the deductive method of the lesson book. The students’ performance in the post-test was compared for both groups in order to determine whether there were significant differences between the groups in relation to the treatment. Significant differences occurring in the experimental group’s post-test speaking performance when compared to the pre-test indicate that the implementation of scaffolding technique can improve students’ speaking ability. The result of this study indicates scaffolding technique has the potential for use in promoting students’ speaking ability